2023
DOI: 10.3390/en16196963
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Al2O3/SiNx Rear-Side Stacked Passivation on the Performance of Polycrystalline PERC Solar Cells

Weitao Fan,
Honglie Shen,
Biao Liu
et al.

Abstract: In recent years, polycrystalline passivated emitter and rear cell (PERC) solar cells have developed rapidly, but less research has been conducted on the preparation process of their rear side passivation layers on standard solar cell production lines. In this work, a Al2O3/SiNx rear side stacked passivation layer for polycrystalline PERC solar cells was prepared using the plasma- enhanced chemical vapor deposition (PECVD) method. The effects of different Al2O3 layer thicknesses (6.8~25.6 nm), SiNx layer thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…For instance, due to the lower parasitic absorption and better rear-side passivation, the sample with SiN X / SiO X N Y /SiN X stacks showed an enhancement of conversion efficiency by 0.09% when compared to the sample passivated with a single 80 nm thick SiN X film. Fan et al 8 analyzed an Al 2 O 3 /SiN X rear side stacked passivation layer obtained by plasma enhanced chemical vapor depositon (PECVD) for multicrystalline PERC solar cells. The results indicated that the most effective passivation was achieved with a 10.8 nm thick Al 2 O 3 layer and a 120 nm thick SiN X layer.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, due to the lower parasitic absorption and better rear-side passivation, the sample with SiN X / SiO X N Y /SiN X stacks showed an enhancement of conversion efficiency by 0.09% when compared to the sample passivated with a single 80 nm thick SiN X film. Fan et al 8 analyzed an Al 2 O 3 /SiN X rear side stacked passivation layer obtained by plasma enhanced chemical vapor depositon (PECVD) for multicrystalline PERC solar cells. The results indicated that the most effective passivation was achieved with a 10.8 nm thick Al 2 O 3 layer and a 120 nm thick SiN X layer.…”
Section: Introductionmentioning
confidence: 99%
“…If the thickness of Al 2 O 3 was decreased to 6.8 nm or increased to 16 nm, the efficiency was reduced by 0.05% and 0.10%, respectively. If the film thickness of SiN X was reduced to 100 nm or increased to 150 nm, the efficiency decreases by 0.05% and 0.09%, respectively 8 . TiO 2 thin films present high refractive index that is optimal for reducing reflection losses of glass-encapsulated solar cells, low extinction factor, high thermal stability and high chemical resistance 9,10 .…”
Section: Introductionmentioning
confidence: 99%